Spatiotemporal patterns and drivers of soil organic carbon in black soil landscapes of Northeast China - Kai Liu; Yunhong Song; Shouying Du; Hongye Xiao; Chaoqun Chen; Jiang Xu; Huimin Dai; Nana Fang (PLoS ONE, 2025)
Soil Organic Carbon (SOC) is crucial for soil health, agricultural productivity, and climate regulation. This study examines the temporal and spatial changes in SOC over a decade (2013–2023) in the Tongken River Basin, a key area within the black soil region of Northeast China. Using machine learning techniques and advanced spatial mapping techniques, the study identified temperature, precipitation, and soil managements as key drivers of SOC dynamics. The results revealed a significant increase in SOC content from 2.99% to 3.25%, and SOC density rose from 7.08 kg/m² to 7.72 kg/m², with precipitation exerting the strongest positive influence. These findings highlight the potential of climate-smart land-use strategies to enhance SOC storage and mitigate soil degradation. This research provides valuable insights for sustainable soil management and climate adaptation efforts in vulnerable agricultural regions.